2020
DOI: 10.1177/0169796x20963332
|View full text |Cite
|
Sign up to set email alerts
|

Social Change in Brazil Through Innovations and Social Movements

Abstract: Social innovations and changes in educational systems are the cornerstones for success of emerging countries. Current developments in Brazil and heterogeneity of society make the country a perfect candidate to investigate these topics. Drawing on historical analysis and content analysis, the author builds a model that recognizes patterns of social change. This model enables to analyze social change through the interaction of radical changes, innovations, social movements, and reforms. This model is applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…As introduced in this article, social innovation can be identified through new institutions, new social relations, new processes or organisational processes, or new networks of institutions that pursue to provide better solutions than the ones before (Maldonado-Mariscal, 2017:39). In this sense, social innovation in education refers to new forms of cooperation or even new governance structures (Schröder and Krüger, 2019;Maldonado-Mariscal, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As introduced in this article, social innovation can be identified through new institutions, new social relations, new processes or organisational processes, or new networks of institutions that pursue to provide better solutions than the ones before (Maldonado-Mariscal, 2017:39). In this sense, social innovation in education refers to new forms of cooperation or even new governance structures (Schröder and Krüger, 2019;Maldonado-Mariscal, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Research on social innovation in education shows how a more systemic approach is needed in innovation, an approach that includes new forms of cooperation and collaboration as well as new governance structures (Schröder and Krüger, 2019;Maldonado-Mariscal, 2020). Additionally, a literature review on social innovation recognized that social innovation can be identified through new institutions, new social relations, new processes or organisational processes, or new networks of institutions that pursue to provide better solutions (Maldonado-Mariscal, 2017:39).…”
Section: Digital Transformation and Skill Mismatch Require Not Only Technological Innovation But Also Social Innovation In Educationmentioning
confidence: 99%
“…The study of social innovation aims to understand how new social practices are configured (Howaldt & Schwarz, 2010) and how change of social practices manifests itself in different dynamics, institutions and contexts. Recent research has examined how social innovations contribute to social change (Howaldt et al, 2015;Maldonado-Mariscal, 2020). Key dimensions identified for social innovations address (1) societal challenges and social demands, (2) concepts and understanding, (3) resources, capabilities and constraints, (4) governance, networks, actors, and (5) process dynamics.…”
Section: Bridging Organisational Education and Social Innovation In E...mentioning
confidence: 99%
“…The methodology of dynamic assessment of the development of consumer demand in the conditions of innovative proposals is applied based on the data of the market demand matrix using the theory of statistical analysis in climate change and stochastic planning (Meiramkulova et al, 2020a;Maldonado Mariscal, 2020;Liu et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%